Application of different containers on eggs hatchability of saline tilapia fish (Oreochromis Niloticus, Linnaeus 1758) - Nurhatijah Nurhatijah; Ahmad Supriatna; Indah Permatasari; Kurnia Kurnia; Humeira Humeira (Faculty of Marine and Fisheries, Universitas Syiah Kuala, 2024)
The community's need for saline tilapia seeds (Oreochromis niloticus) until now still shows a significant increase, the development of tilapia aquaculture business is growing from the sector of breeding and enlargement. This study aims to determine the level of hatchability of saline tilapia eggs (Oreochromis niloticus) with different containers to provide alternatives to the community in using saline tilapia egg hatching containers This research was conducted at the Laboratory of the Fish Seed and Feed Production Technology Study Program of the Polytechnic of Indonesia Venezuela (POLIVEN) in March-April 2024. The research method used was an experimental design, namely a non-factorial Completely Randomized Design (CRD) consisting of 4 treatments, namely A (using a gallon), B (using a teapot), C (using a chicken drinking funnel), D (using a flower pot) each carried out 5 times with test parameters including egg hatchability, larval abnormality, and water quality parameters. Based on the research that has been done, the highest degree of egg hatching is in treatment C (chicken dringking funnel) with a value of 92% an the lowest is in treatment D (flower pot) with a value 51%. The highest larva abnormality is in treatment B (teapot). The annova test result showed that the application of different containers on egg hatchability had a significant effect on the hatching of saline tilapia eggs (Oreochromis niloticus). Based on the results of Duncan's further test showed that the treatment of chicken drinking funnel with 92% percentage is the best treatment compared to other treatments.Keywords:AbnormalityHatchabilityWater qualityTilapia Fish